Does Fiscal Oversight Matter? - Désirée Christofzik; Sebastian Kessing (Center for Economic Studies and ifo Institute (CESifo), 2014)
A gradually introduced reform of local government accounting made it temporarily likely for municipalities in the German state of North Rhine-Westphalia to avoid the effective control of their budget by the authorities in charge with overseeing local government budgets and enforcing the existing fiscal rules. Using this arguably exogenous withdrawal of effective fiscal oversight we identify the effects of fiscal restraints and their enforcement on fiscal outcomes. We find that the withdrawal of oversight has a significant and sizeable effect on per capita debt of local governments that were previously constrained by fiscal oversight. Fiscal restraints are important, and oversight and enforcement are key issues for their success.
Keywords: H72; H74; R10; 330; fiscal oversight; fiscal rules; local government debt